Development and analysis of formulations to the delivery of caffeine for the treatment of gynoid lipodystrophy - Isaac, Vera Lucia Borges [UNESP]; Chiari, Bruna Galdorfini; Boschetti, Viviane Cristine; Uema, Marisa Keiko; Almeida, Maria Gabriela José de; Corrêa, Marcos Antonio; Kedor-Hackmann, Erika Rosa Maria (My University, 2014)
This study aimed to investigate the kinetics of the in vitro release of caffeine in various excipients, and to perform the rheological characterization of these excipients. In vitro release experiments were performed using cellulose membranes in a diffusion apparatus adapted. In order to characterize the rheological behavior of the excipients, a viscometer was used to obtain the flow curves. The data obtained in the present study suggest that caffeine release from the various excipients is dependent of the solubility of caffeine in the excipient (or in the phase of the excipient where caffeine were solubilized) and of the rheological features, mainly the viscosity.
Keywords: Caffeine; Excipient; Gynoide lipodystrophy; In vitro release